Minor stroke syndromes in large-vessel occlusions: mechanical thrombectomy or thrombolysis only? - Messer, Mirko; Schönenberger, Silvia; Möhlenbruch, Markus Alfred; Pfaff, Johannes; Herweh, Christian; Ringleb, Peter A.; Nagel, Simon (American journal of neuroradiology, 2017)
SUMMARY: While mechanical thrombectomy for large-vessel occlusions is now an evidence-based treatment, its efficacy and safety in minor stroke syndromes (NIHSS ≤ 5) is not proved. We identified, in our prospective data base, 378 patients with minor strokes in the anterior circulation; 54 (14.2%) of these had proved large-vessel occlusions. Eight of 54 (14.8%) were immediately treated with mechanical thrombectomy, 6/54 (11.1%) after early neurologic deterioration, and the rest were treated with standard thrombolysis only. Rates of successful recanalization were similar between the 2 mechanical thrombectomy groups (75% versus 100%). Rates of excellent outcome (modified Rankin Scale 0-1) were higher in patients with immediate thrombectomy (75%) compared with patients with delayed thrombectomy (33.3%) and thrombolysis only (55%). No symptomatic intracranial hemorrhage occurred in either group. These descriptive data are encouraging, and further analysis of large registries or even randomized controlled trials in this patient subgroup should be performed.